The Effect of Additives and Reductants on the Strength of Reduced Iron Ore Pellet - Gupta, R.C.; Gautam, J.P. (Iron and Steel Institute of Japan CODEN, 2003)
The higher strength of directly reduced iron (DRI) in pellet form is useful in handling, storing and charging from height without breakage. The DRI pellets commonly exhibit 60 kg cold crushing strength. In this work the effect of reduction temperature, sintering time, quantity/quality of additives and manner of reduction by solid reductant has been studied. The reduced pellet strength could be increased by improving metallic bonds by offering higher reduction temperature (max, 1 250°C) and subsequent sintering. The strength was found to increase by adding slag forming constituents e.g. bentonite. The strength of reductant mixed reduced pellet was observed to be affected by the nature of reductant. The reductant with low bulk density and lower carbon content provided higher voidage rendering lower strength. The cold crushing strength (CCS) of reduced pellets observed in this study ranged from 5 to 200 kg exhibiting ductile to brittle behaviour during deformation.
Keywords: Bentonite; DRI; Ore-carbon pellet; Strength; Water hyacinth char